2.1 Incidence, Causes and Outcomes of Severe Maternal Sepsis Morbidity in the UK. (26th April 2013) - Acosta, CD; Kurinczuk, JJ; Lucas, DN; Sellers, S; Knight, M
Abstract : Background: The incidence of severe genital-tract sepsis has increased in the UK and is now the leading cause of direct maternal death. Underlying this trend is a larger number of severe morbidity cases. The aim of this study was to describe, on a national level, the incidence, causes and outcomes of severe maternal sepsis morbidity in the UK. Methods: A national population-based study was undertaken using the UK Obstetric Surveillance System (UKOSS) between June 2011 and May 2012. Results: 378 women with severe sepsis were identified; an estimated incidence of 5.0 per 10, 000 maternities (95%CI 4.6–5.7). Septic shock was diagnosed in 17.5% (N = 66) of women. Sources of infection were: intrauterine (N = 109; 39.9%), urinary-tract (N = 72; 26.4%), wound (N = 35; 12.8%), and respiratory-tract infection (N = 20; 7.3%). Laboratory-confirmed causative organisms were E. coli (31.3%), group A streptococcus (13.9%), group B streptococcus (13.4%), Staphylococcus aureus (10.4%) and polymicrobial growth (9.6%). Causative organisms differed significantly according to diagnosis of septic shock and mode of delivery (P = 0.002; P < 0.001); group A streptococcus was predominant amongst women with septic shock (30.8%) and spontaneous vaginal deliveries (33.3%), while E. coli was predominant amongst women without septic shock (32.6%), operative vaginal deliveries (36.0%) and caesarean sections (37.1%). Of all severely septic women, 73.0% (N = 276) required critical care and five women died. Conclusions: For every death from maternal sepsis, there are more than 75 women with severe sepsis morbidity. The pattern of infective organisms appears different amongst women who suffer septic shock. Further work is needed to investigate the risk factors associated with sepsis.